Perancangan Video Company Profile PT HLS Batam - Deli Deli; Widya Risma Ilahi (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
In this work practice, the author designed a company profile video that aims to introduce the company, its products, and services to the public. This research is related to PT HLS Batam which is engaged in the fishing industry and is domiciled in Batam. PT HLS Batam does not yet have a promotional media that helps the public to access the company and introduce its products and services. Therefore, we need a company profile video as a promotional media that can introduce PT HLS Batam and provide information about it. In this study using the method of observation, interviews, and literature study. In this case, the work practice that has been implemented will produce a company profile video, which contains a logo as a corporate identity, vision and mission of the company, company address, products to be offered to the public, and company telephone numbers that can be contacted. PT HLS Batam will implement and upload a company profile video to its YouTube account.